2018
DOI: 10.1021/acs.est.8b02566
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Reduction of Cr(VI) Together with Cr(III) Sequestration by Polyaniline Confined in Pores of Polystyrene Beads

Abstract: The simultaneous reduction and sequestration of Cr(VI) from wastewater is desirable as a cost-effective and environmentally friendly approach. In this study, we execute a one-step facile synthesis strategy on polyaniline (PANI) composites based on aniline adsorption and polymerization on pores of millimeter-scale polystyrene balls (PANI@PS). The well-defined PANI@PS increased the removal capacity of Cr(VI) by 5.4 times, going from 43.6 (bulky PANI) to 233.7 mg g −1 near neutral pH (6.0) instead of the pH 1−3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(82 citation statements)
references
References 51 publications
1
81
0
Order By: Relevance
“…Moreover, dealing with highly toxic hexavalent chromium is a difficult task in the treatment of world environmental pollution 13,14 . Based on trivalent chromium's low toxicity and easy flocculation into Cr(OH) 3 in an alkaline environment, reducing Cr (VI) to trivalent chromium has become a key procedure for environmental remediation 15,16 . Among the currently developed reduction methods, the photocatalytic reduction has shown potential application prospects compared with the high-cost chemical reduction method 17 and the biological reduction method 18 with high environmental requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, dealing with highly toxic hexavalent chromium is a difficult task in the treatment of world environmental pollution 13,14 . Based on trivalent chromium's low toxicity and easy flocculation into Cr(OH) 3 in an alkaline environment, reducing Cr (VI) to trivalent chromium has become a key procedure for environmental remediation 15,16 . Among the currently developed reduction methods, the photocatalytic reduction has shown potential application prospects compared with the high-cost chemical reduction method 17 and the biological reduction method 18 with high environmental requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of Cr(VI) in living tissues even in a very small concentration may cause severe neurological or physiological damage. The maximum permissible concentration of Cr(VI) in water is about 0.05 mg•L −1 as accepted by the World Health Organization (WHO) [8]. Perforation of the eardrums and the nasal septum, skin Adsorption data were fitted in the Freundlich, Langmuir, Dubinin-Radishkevitch (D-R), Tempkin, and Elovich isotherm models.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the used hollow PANI micro/nanoshpheres are further treated with 1 M HCl for 0.5 h and then reused for Cr (VI) removal. It can be found from Table 2 that the removal capacity of the first reused hollow PANI micro/nanoshpheres is probably close to the initial PANI removal capacity [26, 37]. It can be concluded that the hollow PANI micro/nanospheres are a reproducible material for Cr (VI) removal.
Scheme 1Schematic illustration the conversion between pernigraniline and emeraldine of PANI
…”
Section: Resultsmentioning
confidence: 78%